Blockholder Structures, Information Asymmetry and Investment Efficiency:Malaysian Insight - Mubashir Ali, Khan (Universiti Malaysia Sarawak, (UNIMAS), 2023)
This thesis examines the influence of blockholder concentration, blockholder identity and information asymmetry on investment efficiency. It also examines the moderating role of blockholder concentration in the relationship between information asymmetry and investment efficiency. Based on agency theory, this study extends the previous literature on blockholders. The literature to date has focused on the agency conflicts between managers and shareholders, ignoring the agency conflict that might arise between principal and principal. Furthermore, the previous research has focused on the monitoring role of blockholders by ignoring its governance role. As a result, this study fills this gap in the literature by collecting the sample of Malaysian firms listed at Bursa Malaysia in the period 2010-2018. This study measures blockholder structures through the dimensions of blockholder concentration and blockholder identity. This study categorizes blockholders identity into financial and non-financial blockholders. Information asymmetry is measured through three dimensions, quoted spread, analyst forecast error and analyst forecast dispersion. The empirical findings of this study document a significant negative relationship between blockholder concentration and investment inefficiency. This study also documents that both identities of blockholder can influence investment efficiency of a firms. However, this effect is more pronounced when firms are owned by non-financial blockholder rather than financial blockholders. These results also support the notion that information asymmetry tends to increase sub-optimal investments. Furthermore, the findings also suggest that blockholder concentration negatively moderate the relationship of information asymmetry with investment inefficiency. The results of this study are robust with an alternative measure of investment efficiency. A practical implication of this research for researchers, managers, investors, and policy makers is that it explores the relationship between blockholder structures, information asymmetry and investment efficiency. This study provides very interesting insight about blockholders concentration at different equity percentage of (25,35, 45, 50, 55, 65, 75). It will help researchers to advance their knowledge on the determinants of investment efficiency that investment efficiency is higher in firms in which non-financial blockholders have more equity shares as compared to firms owned by financial blockholders.